If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8a-4(-5a-2)=-2(4-7a)
We simplify the equation to the form, which is simple to understand
8a-4(-5a-2)=-2(4-7a)
Reorder the terms in parentheses
8a+(+20a+8)=-2*(4-7a)
Remove unnecessary parentheses
+8a+20a+8=-2+*(+4-7a+)
Reorder the terms in parentheses
8a+20a+8=+(-8+14a)
Remove unnecessary parentheses
+8a+20a+8=-8+14a
We move all terms containing a to the left and all other terms to the right.
+8a+20a-14a=-8-8
We simplify left and right side of the equation.
+14a=-16
We divide both sides of the equation by 14 to get a.
a=-1.14285714286
| a-5/3-5(a-4)/8=2a+8/4 | | 1/2X+6=-13 | | 5-4(3x-9)= | | 2(x-3)+3(x+9)=-29 | | 7f-1=45 | | (y+5/3)-3=6 | | 5e-6-4=-3 | | x(2x-2)+x(3x-4)=(5x+6)(x-4) | | -126=14*k | | 6z+5(z-6)= | | (5e-6)-4=-3 | | 4x-1-4x+7= | | 4x+x=-27 | | 21=-7*n | | -13=-8b-5b | | -6x-50+12x=64 | | 4x-4=27 | | 0.15x+0.6(x-2)=0.01(3x-5) | | 5(-5)-2(2)= | | 11t/28-t/4=1 | | x-2(3x-2)=-6+4x-8 | | -15*x=2 | | g(-x)=x^2+10x+35 | | 5-4(3m-6)=5 | | 4(3+1.25)+5y=12.00 | | 6y+3-8=-37 | | 5x+6x-(3x+5)= | | V+9=1 | | x^3-6x+9x=0 | | 6n+4+2=-24 | | -10-5(1+j)= | | -2x+1=-2(x+5) |